Poverty and the role of social protection systems in Africa during the COVID-19 pandemic - Abay, Kibrom A.; Yonzan, Nishant; Kurdi, Sikandra; Tafere, Kibrom (International Food Policy Research Institute, 2022)
Key messages  The pandemic increased poverty in Africa by less than expected, approximately 1.5-1.7 percentage points in 2020.  Countries affected by Fragility, Conflict, and Violence (FCV) experienced the greatest increases in poverty.  An emerging literature establishes that social protection programs in Africa during the pandemic had positive impacts and was generally pro-poor, suggesting a key cushion-ing role played by the expansion of social protection on trends in poverty.  However, delivering shock-responsive social protection in Africa continues to face im-portant challenges related to targeting, coverage, timeliness, and financing.  Early targeting analyses for some countries during the pandemic show that targeting was broadly progressive in some countries and regressive in some other countries.